An optimal-oriented quasi-droop control of interlinking converter in hybrid microgrid - Lin, Fanfan (2019)
In hybrid microgrid, interlinking converter (ILC) is a key component to connect the AC subgrid and DC subgrid. Its control strategy significantly affect the power flow management, power quality, system efficiency and stability. Traditionally, ILC is usually controlled as a current source, resulting in a poor dynamic stability when a remote weak AC subgird is connected by a large linking impedance. In this study, a quasi-droop control scheme is proposed to control ILC as a current controlled voltage source (CCVS). Not only a flexible power flow management is achieved, but an ancillary function of voltage support is also provided. Moreover, this simple quasidroop control enables ILC to synchronize with the AC subgrid autonomously without a phase-locked loop (PLL). Finally, simulations are presented to verify the system effectiveness.